Immigrant Elders: What Can Maine Learn from Other States? - Silka, Linda (Maine Policy Review, 2015)
Maine is not yet home to large numbers of immigrants, but that may soon change. Linda Silka presents lessons from elsewhere about elder immigrants and considers their implications for Maine. She suggests that attention to the topic of immigrant elders will help Maine to create policy and opportunity for all elders.
Keywords: Maine; aging; immigrants; demographic changes; Lowell